Effectiveness of a Neuroeducation-Based Instructional Intervention on Cognitive Flexibility and Creative Resilience Among Undergraduate Students: A Quasi-Experimental Study - Grace Freya Purba; Giselle Dupont; Despian Januandri (Enigma Institute, 2026)
Neuroeducation-based instructional approaches have gained attention for enhancing cognitive outcomes, yet empirical evidence in higher education remains limited. This study aimed to evaluate the effectiveness of an eight-week neuroeducation-based instructional intervention on cognitive flexibility, creative resilience, and academic engagement among undergraduate students. A quasi-experimental pre-test post-test control group design was employed. A total of 124 undergraduate students at a private university in Palembang, Indonesia were assigned to an experimental group (n = 62) receiving the neuroeducation-based intervention and a control group (n = 62) receiving conventional instruction. Cognitive flexibility was measured using the Cognitive Flexibility Inventory (CFI), creative resilience using the Creative Resilience Scale (CRS), and academic engagement using the Academic Engagement Scale (AES). Data were analyzed using analysis of covariance (ANCOVA) controlling for pre-test scores, with bootstrapped effect size confidence intervals (10,000 resamples). The experimental group showed significantly higher post-test scores compared to the control group on cognitive flexibility (p < 0.001, d = 1.72, 95% CI [1.28, 2.16]), creative resilience (p < 0.001, d = 1.89, 95% CI [1.44, 2.34]), and academic engagement (p < 0.001, d = 1.12, 95% CI [0.70, 1.54]). In conclusion, neuroeducation-based instructional interventions can substantially enhance cognitive flexibility and creative resilience among university students, supporting the integration of neuroscience-informed pedagogy into higher education curricula.